If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2n + 2 = 6n + 1 Reorder the terms: 2 + 2n = 6n + 1 Reorder the terms: 2 + 2n = 1 + 6n Solving 2 + 2n = 1 + 6n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-6n' to each side of the equation. 2 + 2n + -6n = 1 + 6n + -6n Combine like terms: 2n + -6n = -4n 2 + -4n = 1 + 6n + -6n Combine like terms: 6n + -6n = 0 2 + -4n = 1 + 0 2 + -4n = 1 Add '-2' to each side of the equation. 2 + -2 + -4n = 1 + -2 Combine like terms: 2 + -2 = 0 0 + -4n = 1 + -2 -4n = 1 + -2 Combine like terms: 1 + -2 = -1 -4n = -1 Divide each side by '-4'. n = 0.25 Simplifying n = 0.25
| 1Z-5Z=-4Z | | 4x-8=2x-8+2x | | 1Z-5Z= | | 5-5x=5x-95 | | 3+4x+5x=-4 | | -16=-9m | | -6(7x+8)=162 | | X+14=-49 | | v^2-6vx+9x^2=0 | | 5x+2(5x-9)=72 | | 2(3x-2)=yx | | s=w/2(a | | 60a^2-10a=0 | | y^2-6yw+9w^2=0 | | -2.2=x/6+7.4 | | 9y^2-42yw+49w^2=0 | | 17-29=3z | | 10=-14x | | -6=m/5 | | .04x+.01(18-x)=18(.02) | | x-14=-40 | | -15=3+3v | | (b-5)(b+9)= | | v/2-6=2 | | 8x-74=x+77 | | 43=5v+8 | | 4(5+3n)=92 | | x+77=8x-74 | | 6y=-12+9x | | h=-16t^2+28t+32 | | -15c=2 | | 3x+5y=63 |